Problem-based learning assisted by virtual laboratory media: Its effect on students’ understanding of concepts in excretory system material - Ratna, Ratna Dewi Munthe; Adlini, Miza Nina (Univeritas Papua, 2024)
Learning concepts is an integral part of learning biology, including abstract (requiring analytical skills) and tangible (requiring observational experience) ideas. If the learning model used is not appropriate, it can cause boredom, a lack of understanding of the subject matter, and a monotonous appearance that makes students reluctant to learn. This is why students have difficulty understanding concepts. This study aims to ascertain whether problem-based learning with virtual laboratory media influences students' conceptual understanding. The type of research conducted was quasi-experimental. A total of 49 students from class XI, divided into two classes, became the population. Since complete sampling was used, 49 students became the sample. Problem-based learning strategies and virtual laboratory materials were used to teach the experimental class in XI-1. The control group in class XI-2 used conventional learning techniques. Five essay-based test questions served as research tools. After data collection, the impact of the problem-based learning paradigm supported by virtual laboratory media on students' conceptual knowledge was assessed using an Independent t-test and normality test. Students' conceptual understanding can be improved using the problem-based learning technique with virtual laboratory media to streamline the learning process and enable practical activities.